Outcomes of patients with nasopharyngeal carcinoma treated with intensity-modulated radiotherapy. (30th March 2021) - Yeh, Shyh-An; Hwang, Tzer-Zen; Wang, Chih-Chun; Yang, Chuen-Chien; Lien, Ching-Feng; Wang, Chien-Chung; Hsu, Tun-Yen; Hsu, Ruey-Feng; Shih, Yu-Chen; Huang, Yaw-Chang; Hsieh, Meng-Che; Gau, Jhy-Shyan; et al.
Abstract: Nasopharyngeal cancer shows a good response to intensity-modulated radiotherapy. However, there is no clear evidence for the benefits of routine use of image-guided radiotherapy. The purpose of this study was to perform a retrospective investigation of the treatment outcomes, treatment-related complications and prognostic factors for nasopharyngeal cancer treated with intensity-modulated radiotherapy and image-guided radiotherapy techniques. Retrospective analysis was performed on 326 consecutive nasopharyngeal cancer patients treated between 2004 and 2015. Potentially significant patient-related and treatment-related variables were analyzed. Radiation-related complications were recorded. The 5-year overall survival and disease-free survival rates of these patients were 77.9% and 70.5%, respectively. Age, AJCC (American Joint Committee on Cancer) stage, retropharyngeal lymphadenopathy, treatment interruption and body mass index were independent prognostic factors for overall survival. Age, AJCC stage, retropharyngeal lymphadenopathy, image-guided radiotherapy and body mass index were independent prognostic factors for disease-free survival. In conclusion, intensity-modulated radiotherapy significantly improves the treatment outcomes of nasopharyngeal cancer. With the aid of image-guided radiotherapy, the advantage of intensity-modulated radiotherapy might be further amplified.